Digoxin and Platelet Activation in Patients With Atrial Fibrillation: In Vivo and In Vitro Study - Pastori, Daniele; Carnevale, Roberto; Nocella, Cristina; Bartimoccia, Simona; Novo, Marta; Cammisotto, Vittoria; Piconese, Silvia; Santulli, Maria; Vasaturo, Fortunata; Violi, Francesco; Pignatelli, Pasquale (Journal of the American Heart Association, 2018)
Background Digoxin use was shown to be associated with an increased risk of cardiovascular events in atrial fibrillation ( AF ). We hypothesized that digoxin may affect cardiovascular risk by increasing platelet activation. Methods and Results Post hoc analysis of a prospective study of anticoagulated patients with AF . Patients were divided into 2 groups balanced for age, sex, and cardiovascular risk factors: digoxin users (n=132) and nonusers (n=388). Urinary excretion of 11-dehydro-thromboxane B (TxB ), a marker of platelet activation, and serum digoxin concentration ( SDC ) were measured. In vitro experiments were performed on platelets from healthy subjects and AF patients, which were incubated with scalar doses of digoxin (0.6-2.4 ng/mL) with or without prestimulation with a sub-threshold of collagen. Median 11-dehydro-TxB was 105.0 ( interquartile range, 60.0-190.0) ng/mg creatinine, and median SDC was 0.65 ( interquartile range, 0.40-1.00) ng/mL. Urinary 11-dehydro-TxB and SDC were correlated ( r =0.350, P<0.001). Patients in the upper tertile of SDC showed higher 11-dehydro-TxB compared with non-digoxin users ( P=0.019). In vitro study showed an increased basal platelet activation in patients with AF compared with healthy subjects . Digoxin (2.4 ng/mL) induced calcium mobilization, PAC -1 (procaspase-activating compound 1) and platelet aggregation in AF patients but not in healthy subjects . After pretreatment with a sub-threshold of collagen, digoxin dose-dependent induced calcium mobilization, arachidonic acid release, TxB biosynthesis, PAC -1 and soluble platelet selectin expression, and platelet aggregation, which were inhibited by antibody against digoxin. Conclusions We found a significant in vivo correlation between SDC and platelet activation. Supratherapeutic SDC increased in vitro platelet aggregation via calcium-related phospholipase A phosphorylation. Our findings may have clinical implications for AF patients treated with digoxin.